The Impact of the Paulowniaceae Family Species Introduction on Biodiversity and the Structure of Local Ecosystems - Salybekova, Nurdana; Babayeva, Gulmira; Tomasheva, Nurila (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
This research examines the potential for the introduction of Paulownia tomentosa into the climatic conditions of the Turkistan city. The ecological, economic, and ornamental characteristics of the P. tomentosa were analyzed, and its ability to grow in fertile soils was highlighted. The experiment employed a method of vegetative propagation using root cuttings, with particular attention given to the main ecological factors influencing plant development (temperature, humidity, and substrate type). The results demonstrated that rooting and initial growth of paulownia were most effective in peat-based substrate under moderate temperature and humidity conditions. According to the research results, the most favorable conditions for rooting and initial growth of Paulownia tomentosa include the use of peat as a substrate, moderate temperatures (20–25 °C), and optimal humidity levels. Although high humidity promotes rapid plant growth, it also increases the risk of diseases such as wilting and rot. The use of soil-based substrates, particularly under high humidity conditions, showed lower effectiveness. It was also determined that suboptimal (lower) temperatures significantly slow down plant development. Additionally, morphological differences were observed depending on the temperature regime: under normal temperatures, a greater number of smaller leaves was noted, while under lower temperatures, the number of leaves decreased, but their size increased. These findings can serve as a scientific basis for the large-scale cultivation of paulownia in the Turkistan region.